2021
DOI: 10.1007/s00606-021-01770-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability, cytotype diversity, and cytogeography of populations traditionally called Dactylorhiza fuchsii in Central Europe

Abstract: The morphological variation and cytotype diversity were investigated among Central European populations traditionally recognized as Dactylorhiza fuchsii, recently incorporated in D. maculata s.l. Flow cytometry was employed to assess the ploidy levels of 738 individuals from 77 localities and multivariate morphometrics for a total of 531 individuals from 27 localities. Three ploidy levels were found: diploid (2n = 2x = 40), DNA-triploid and tetraploid (2n = 4x = 80). Whereas diploids and tetraploids often occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Dufrêne et al (1991) conducted a biostatistical study of 12 D. fuchsii populations based on 28 morphometric traits for Western Europe. Taraška et al (2021) conducted a comparative analysis of D. fuchsii populations based on 24 morphological characters for 27 sites from Central Europe: Austria, Czech Republic, Germany, Hungary, Poland, Romania, Slovakia, and Slovenia. Kirillova and Kirillov (2013) conducted a population study of 28 D. fuchsii populations based on 19 morphometric characters in the European part of Russia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dufrêne et al (1991) conducted a biostatistical study of 12 D. fuchsii populations based on 28 morphometric traits for Western Europe. Taraška et al (2021) conducted a comparative analysis of D. fuchsii populations based on 24 morphological characters for 27 sites from Central Europe: Austria, Czech Republic, Germany, Hungary, Poland, Romania, Slovakia, and Slovenia. Kirillova and Kirillov (2013) conducted a population study of 28 D. fuchsii populations based on 19 morphometric characters in the European part of Russia.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out concerning the biology of D. fuchsii in anatomy (Aybeke et al 2010;Naczk et al 2010), morphometry and biostatistics (Dufrêne et al 1991;Tyteca and Gathoye 1999;Sumbembayev et al 2021), ontogenesis (Vakhrameeva 2006;Jacquemyn et al 2012), micropropagation (Jakobsone 2008;Jakobsone et al 2010), geographic distribution (Đorđević et al 2014), and genetics (De Hert et al 2012;Box et al 2012;Efimov et al 2016;Wróblewska et al 2019). At the same time, a limited number of population studies of the species were carried out (Bateman and Denholm 1989;Dufrêne et al 1991;Janečková et al 2006;Kirillova and Kirillov 2013;Kotukhov et al 2018;Kosolapova et al 2021;Taraška 2021), especially in the peripheral part of the range. Special studies on the study of populations of D. fuchsii, the ecological characteristics of communities and the floristic composition of these populations in the territory of the Kazakhstan part of the Altai mountainous country have not been previously carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogeny and patterns of evolution of the genus Dactylorhiza Necker ex Nevski have been studied using a varie ty of methods, beginning in the 1990s and early 2000s using allozymes (e.g., Pedersen 1998), karyotype morphology (D'Emerico 2002), and genetic fingerprinting techniques (e.g., Hedrén et al 2001), followed by comparisons between different nuclear and plastid loci (e.g., Pillon et al 2007), epi gene tics (e.g., Paun et al 2011), genome size estimation by flow cytometry (e.g., Taraška et al 2021), transcriptome analysis (Balao et al 2017), and restriction site-associated DNA sequencing by RADseq (Brandrud et al 2020). Morphology has been studied repeatedly in relation to evolution in some of the above studies, as well as in many others.…”
Section: Dactylorhiza Maculata Species Aggregate (Orchidaceae: Orchid...mentioning
confidence: 99%
“…Polyploidy in some plant groups occurs quite frequently and may result in only minimal, if any, morphological diffe ren ces. Recently, a tetraploid lineage of D. fuchsii was disco vered in the mountains of Central Europe (Ståhlberg & Hedrén 2010, Taraška et al 2021. Taraška et al (2021) per for med a rather thorough morphological analysis, but never the less concluded that it was indistinguishable from di ploids neither morphologically nor ecologically.…”
Section: Key For Species Identification Ofmentioning
confidence: 99%
See 1 more Smart Citation